Promoting gender equality: An examination of feminist rhetoric in Kaleni Hiyalwa’s novel Meekulu’s Children (JULACE: Journal of the University of Namibia Language Centre, 2020)
Women’s rhetorical contributions have been overlooked in the field of rhetoric because the rhetorical tradition has a long history of excluding female or feminine ways of speaking and writing. It is also worth noting that the analyses of women’s writings have been restricted to the coverage of the feminist perspectives and not necessarily the domain of rhetoric and the analysis of their works of fiction. This has therefore, led to the realisation of a gap in the present paper regarding the examination of feminist rhetoric in literary studies. Through a rhetorical lens, this paper examined the arguments that demonstrate that women have immensely contributed to the liberation struggle in Namibia alongside men; hence, there is a need for equal acknowledgment. Based on the Aristotelian rhetorical theory, the study established how the arguments (logos) provided in Kaleni Hiyalwa’s novel, Meekulu’s Children, provide evidence that women indeed actively participated in the liberation struggle and how these proofs stir the readers’ emotions (pathos). Furthermore, the determination and willingness of characters (ethos) to collaborate with other characters to promote gender equality was examined. Invitational rhetoric was also used to determine whether the novel has promoted feminist principles of equality, self-determination and immanent value. The paper found that arguments can be made to provide evidence for feminist rhetorical analysis with regards to how Dila and his wife were murdered by the omakakunya; the raping of his wife, how Meekulu cooks for eendume domomufitu, and also how Kamati and Estela make seemingly insensible choices to run out of the country. As a result, these supportive arguments stimulate emotions as exemplified by the descriptions of the murder of Dila and his wife and how Ketja copes with the death of both parents, which stirs empathy from the readers. Moreover, the novel presents how the men and women of Elombe have been supportive of each other in good and bad times throughout the time of war thereby bringing to the fore views geared towards appreciating the African sense of Ubuntu. Lastly, the study determined that invitational rhetoric allows readers to participate in conversations in the novel through the use of rhetorical strategies like: emotional utterances, respect of different ideologies, and rhetorical questions.
Keywords: equality; liberation struggle; rhetoric; complement; feminist; politic